Answer:
Step-by-step explanation:
Given the quadratic equation
4r²+11x+7=0
Question is wrong, so let rewrite the question and let it have just one variable, let use x
4x²+11x+7=0
Divide through by 4
4x²/4 + 11x/4 +7/4=0
x²+11x/4 + 7/4=0
x²+11x/4=-7/4
To write the LHS in perfect square, divide the coefficient of x which is 11/4 by 2, after dividing by 2, we will now square the result and add it to both sides of the equations
DIVIDE BY 2=11/4÷2 =11/8
Square=(11/8)²
Then, let add
x²+11x/4 +(11/8)²=-7/4+(11/8)²
Then, the LHS is now a perfect square, so we can weite as
(x+11/8)²=-7/4 +121/64
(x+11/8)²= (-112+121) /64
(x+11/8)²= 9/64
Square root both sides
x+11/8= ±√(9/64)
x= ±√(9/64) - 11/8
Then,
x= ±3/8 - 11/8
So it is either
x=3/8-11/8
x=(3-11)/8
x=-8/8
x=-1
Or
x=-3/8-11/8
x=(-3-11)/8
x=-14/8
x=-7/4
x=-1.75
Then the answer to the quadratic equation using completing the square method is
x=-1 or -1.75